A Membrane‐Intercalating Conjugated Oligoelectrolyte with High‐Efficiency Photodynamic Antimicrobial Activity. Issue 18 (28th March 2017) - Wang, Bing; Wang, Ming; Mikhailovsky, Alexander; Wang, Shu; Bazan, Guillermo C.
Abstract: A membrane‐intercalating conjugated oligoelectrolyte (COE), PTTP, was designed and synthesized with the goal of providing red‐shifted absorption spectra relative to previously synthesized COE analogs. Specifically, electron‐rich and electron‐poor subunits were introduced in the conjugated backbone to modulate the band gap.PTTP exhibits maxima of absorption at 507 nm and of emission at 725 nm.PTTP can also efficiently function to generate singlet oxygen in situ (ΦΔ ≈20 %) and has appropriate topology and dimensions to interact with lipid membranes. The resulting rapid membrane insertion and sensitizing ability providePTTP with a highly efficient antibacterial capability under a low light dose (0.6 J cm −2 ) toward Gram‐negative bacteria E. coli, making it a remarkably efficient optically mediated antimicrobial agent. Abstract : Light on, bugs out : A membrane‐intercalating conjugated oligoelectrolyte (COE), PTTP, was designed to exhibit red‐shifted absorption spectra relative to previously synthesized COEs. PTTP accumulates in the membrane of E. coli and is efficient toward singlet‐oxygen photogeneration. This combination of properties gives rise to excellent optically mediated antibacterial capability under low light dosage.